2018
DOI: 10.3233/jad-170695
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Butyrylcholinesterase in Progression of Mild Cognitive Impairment to Alzheimer’s Disease

Abstract: Although BuChE-K alone does not seem to play a major role in progression to AD in MCI patients, a synergistic effect with the ApoE ɛ4 allele was found, highlighting the importance of assessing these combined genotypes for evaluating risk progression in MCI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Butyrylcholinesterase (BChE) is an enzyme which splits choline compounds as well as other esters 19. For a long time BChE was thought to have a less important function, but recent literature demonstrated that BChE may in part and with a significantly slower rate and affinity act as a substitute in the absence of AChE with a relevant role in the development of a cholinergic deficit 20 21…”
Section: Introductionmentioning
confidence: 99%
“…Butyrylcholinesterase (BChE) is an enzyme which splits choline compounds as well as other esters 19. For a long time BChE was thought to have a less important function, but recent literature demonstrated that BChE may in part and with a significantly slower rate and affinity act as a substitute in the absence of AChE with a relevant role in the development of a cholinergic deficit 20 21…”
Section: Introductionmentioning
confidence: 99%
“…In APOE4 carriers, reduced BuChE activity is more marked in BCHE-K carriers, with a BCHE-K allele dose-dependent reduction in BuChE activity and lowering of glial activation markers (24, 29). The BCHE-K and APOE4 alleles significantly interact to reduce the age-at-onset of AD (30), and to increase the likelihood of progression from mild cognitive impairment (MCI) to AD (27, 31) and from cognitively unimpaired older individuals to early AD (26). Carriers of both APOE4 and BCHE-K alleles in the MCI stage of AD have a limbic-amnestic phenotype and progress most rapidly in the mild stage of AD, where they are the only genotype group with a significant response to AChE-I treatment (27, 3133).…”
Section: Introductionmentioning
confidence: 99%
“…In APOE4 carriers, reduced BuChE activity is more marked in BCHE-K carriers, with a BCHE-K allele dose-dependent reduction in BuChE activity and lowering of glial activation markers [ 24 , 29 ]. The BCHE-K and APOE4 alleles interact to significantly reduce the age-at-onset of AD [ 30 ], and to increase the likelihood of progression from mild cognitive impairment (MCI) to AD [ 27 , 31 ] and from cognitively unimpaired older individuals to early AD [ 26 ]. Carriers of both APOE4 and BCHE-K alleles in the MCI stage of AD have a limbic-amnestic phenotype and progress most rapidly in the mild stage of AD, where they are the only genotype group with a significant response to AChE-I treatment [ 27 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%